The Increasing Production of Soybean Plants (Glycine max L.) Based on Result Target’s and Nutrient Index (Jurnal Online Pertanian Tropik, 2019)
The aim of this research was to prove the giving fertilizer with dosage that produces seed production of soybean (Glycine max L.) 3 ton/ha and studying soil fertility through the nutrient indexs. The research was conducted in June 2017 until September 2017 at the market land of 1 Tanjung Sari, Medan Selayang sub-district. The research design is Factorial Random Design with two factors. The first factor is doses of fertilizer with the target of P1 = target 2 ton/ha; P2 = target 3 ton/ha; P3 = target of 4 ton/ha, second factor is treatment of soil nutrient index consist of B1 = 0,8 (100% less 20%); B2 = 0.9 (100% less 10%); B3 = 1 (100% standard nutrient index); B4 = 1.1 (100% plus 10%); B5 = 1.2 (100% plus 20%). The results showed that interaction of fertilizer based result target dose 3 ton/ha and nutrient index 0,9 (Urea : 45 kg/ha, SP-36: 90 kg/ha, KCL: 27 kg/ha, Phonska: 90 kg/ha, Dolomite: 900 kg/ha) reaches production of 2.86 tons/ha. The soil nutrient index found in B2 = 90% (fertilizer dose reduced by 10%) showed that the soil was fertile and gave the nutrient 10%.